Rancang Bangun Charging Current Monitor Berbasis Mikrokontroler - Nugraha, Sayid Fadil; Dalimunthe, Muhammad Erpandi (Politeknik Harapan Bersama Tegal, 2025)
Some problems occur when the solar cell is connected directly to a battery for charging process. They are caused by the output of solar cell depend on intensity of sunlight. When the intensity reach the maximum value, the current of charging will exceed the permitted current. Therefore, it will shortened the lifetime of the battery. Beside that, when the intensity is droped, the charging process need a long time, moreover it will not performed. This paper investigates the design of charging current monitor that is used as the solution of the problem mentioned above. The system is used for detecting the output current from the solar cells as a charging current monitor following the fluctuation of sunlight intensity. The system use the principal of voltage subtraction and inverting amplifier supported by ATmega 8535 Microcontroller. This paper also investigates about solar cells characterization device which is used to measure the performance of the solar cells.